Lighting control system using microcontroller - Lim Yee Hwa (Universiti Malaysia Perlis, 2009)
Lighting control system is a system that reduces energy consumption by optimizing the daylight. Automatic shading, dimming control system and pre-programmed mode have been developed in order to reduce the energy consumption. In this project, microcontroller was used to implement control strategies such as open or close the window automatically and control the brightness of the lamp. The pre-programmed mode was designed based on different condition such as sleeping mode, romance, privacy and daylight mode. The different operation mode was executed according to different condition. The light sensor and infrared sensor were used respectively to detect the illumination of daylight and number of people inside a room or space so that appropriate operation can be implemented. This lighting control system is able to open or close the window automatically by sensing the intensity of daylight and the chosen pre-programmed mode can help to reduce energy consumption. Besides that, the dimming control system also able to reduce the electricity consumption successfully.